1997
DOI: 10.1021/ic970284x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Solution Characterization of Mononuclear Vanadium(IV) Complexes That Help To Elucidate the Active Site Structure of the Reduced Vanadium Haloperoxidases

Abstract: The complexes [VO(H(2)O)ada] (1), [VO(H(2)O)Hheida] (2), and [VO(H(2)O)aeida] (3) (H(2)ada, N-(carbamoylmethyl)iminodiacetic acid; H(3)heida, N-(2-hydroxyethyl)iminodiacetic acid; H(2)aeida, N-(2-aminoethyl)iminodiacetic acid) were synthesized and crystallographically characterized. Crystallographic parameters for 1.2H(2)O: monoclinic, space group P2(1)/c (No. 14), a = 7.327(2) Å, b = 23.386(7) Å, c = 7.258(3) Å, alpha = 90 degrees, beta = 110.95(2) degrees, gamma = 90 degrees, V = 1204.6(7) Å(3), Z = 4, R1 = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 42 publications
9
87
0
1
Order By: Relevance
“…However, in the 51 V NMR spectra of solutions containing 3 mm of V V and 6 mm of 1, a new signal at d~À577 ppm was detected in the pH range 5±9, indicating complex formation. With pyridoxamine, the 51 V NMR measurements with 3 mm V V and 12 mm of ligand did not show any complex formation in the same pH range. In the V V ±H 2 Rpyr 2 en system pH-potentiometry clearly indicated complex formation, and the stability constants given in Table 3 were obtained by the evaluation of the pH-metric titration data.…”
Section: Ligand Protonation By Ph-potentiometry and 1 H Nmr Spectroscmentioning
confidence: 79%
See 3 more Smart Citations
“…However, in the 51 V NMR spectra of solutions containing 3 mm of V V and 6 mm of 1, a new signal at d~À577 ppm was detected in the pH range 5±9, indicating complex formation. With pyridoxamine, the 51 V NMR measurements with 3 mm V V and 12 mm of ligand did not show any complex formation in the same pH range. In the V V ±H 2 Rpyr 2 en system pH-potentiometry clearly indicated complex formation, and the stability constants given in Table 3 were obtained by the evaluation of the pH-metric titration data.…”
Section: Ligand Protonation By Ph-potentiometry and 1 H Nmr Spectroscmentioning
confidence: 79%
“…The aqueous V V ±H 2 Rpyr 2 en system was also studied by 2D 1 H NMR techniques, including COSY, NOESY, TOCSY, and ROESY, using the respective pulse sequences installed in the software of the NMR instrument. 51 V NMR acquisition parameters were: 33 kHz spectral width, 30 ms pulse width, 1 s acquisition time, and 10 Hz line broadening. The signal intensities of the NMR resonances were obtained using the program NUTS.…”
Section: Synthesis Of the Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies, it was found that the investigation of ADA-metal chelates in solid state provides information about the chelating role of the divalent anion H 2 NCOCH 2 N(CH 2 COO ) 2 . Therefore, some mixedligand complexes of transitional metal ions with ADA as primary ligand and water molecule, imidazole and 2,2¢-bipyridine as secondary ligands have been reported [1,[4][5][6][7][8]. However, crystal structures of the mixed-ligand metal(II) complexes with ADA and 1,10-phenanthroline compound have not been studied so far.…”
Section: Discussionmentioning
confidence: 99%